Legal Protection For Land Rights Holders Upon Disposal Of Land Rights For Public Interest (Case Study Of Depok Toll Road Land Acquisition) - Novianti, Dinda; Sulistiyono, Adi; Hermawan, Sapto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Indonesia as a legal state is clearly guided by existing rules in policies relating to the rights of its citizens. This research aims to determine the form of legal protection for land ownership rights for development in the public interest of the Depok Toll Road and to determine the mechanism for providing compensation for land ownership rights for development in the public interest. The method used in this research is a normative research method with a conceptual and statutory approach, as well as using quantitative quantitative analysis in the form of quantitative analytical literature. Compensation for land for public purposes must be based on the principle of justice, where there are adequate guarantees to the entitled parties, the obstacle that arises is the lack of funds from the government for land acquisition.